Characterization of Natural Fibers from Cortaderia Selloana Grass (Pampas) as Reinforcement Material for the Production of the Composites - Anish Khan; R. Vijay; D. Lenin Singaravelu; M. R. Sanjay; Suchart Siengchin; Francis Verpoort; Khalid Ahmad Alamry; Abdullah M. Asiri (Journal of Natural Fibers, 2021)
Due to environmental problems by the use of synthetic fibers in composite materials, researchers are more concerned with searching for eco-friendly materials. Consequently, the use of reinforcing fibers of natural origin is the best option that promotes the obtaining of materials that do not harm the environment. This paper presents characterization of Cortaderia selloana grass (Pampas) fibers by physical-chemical analysis, FTIR, XRD, thermogravimetric analysis, single fiber tensile test and SEM analysis. Diameter (372.6 µm), density (1261 kg/m3), cellulose content (53.7 wt.%), crystallinity index (22%), tensile strength (20 ± 1.0 MPa), Young’s modulus (8.88 GPa), and thermal stability (320°C) properties were identified in the Cortaderia selloana grass (Pampas) fibers. Overall properties of these fibers showed that it could be an alternative source as reinforcement material for the manufacture of composite materials.